Characterization of the population of pregnant women attending a mental health service - Ferreira, Tiago (2020)
Introduction: Psychopathological symptoms are common during pregnancy and their detection and referral to specialized care is often suboptimal. The aim of this study was to perform a descriptive analysis of sociodemographic, mental health, and obstetric features of a population of pregnant women followed at Psychiatry consultation. Methodology: This was a cross-sectional, descriptive study of women followed both at Gynecology/Obstetrics and Psychiatry consultations of Hospital Prof. Doutor Fernando Fonseca between 2014 and 2016. A total of 76 women were included, for whom pre-defined features associated in the literature with risk of developing psychopathological symptoms during pregnancy were collected. Results and Discussion: Risk factors identified in the development of depressive symptoms included absence of an affective relationship during pregnancy (n=11; 14.5%), being first-generation immigrant (n=17; 22.4%), and substance use before (n=18; 23.7%) or during (n=10; 13.1%) pregnancy. Sample was divided into women with previous Psychiatry follow-up who became pregnant (n=44; 57.9%) and women referred to Psychiatry consultation during pregnancy (n=32; 42.1%). In the second group, 18.8% (n=6) of referrals were from primary health care, being relevant to understand whether this represents an under-referral. Prescription of 21 risk category D drugs was identified, alerting to the need of caution in pharmacological prescription and of considering non-pharmacological options (e.g., cognitive-behavioral therapy) for management of these cases. Conclusions: Risk factors identified in this study represent an opportunity to optimize clinical practice and improve these patients’ follow-up.